2006
DOI: 10.1002/casp.876
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous reconciliation in Australia: do values, identity and collective guilt matter?

Abstract: This paper reports an investigation of the impact of shared values and identities on Australian attitudes towards Indigenous reconciliation across two studies. In Study 1, University students were assigned to one of two conditions in which they completed a questionnaire that measured their value priorities and reconciliation attitudes; either as an individual or as an Australian. As expected, the value of egalitarianism was the strongest predictor of reconciliation attitudes, especially under the Australian co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 17 publications
3
39
1
3
Order By: Relevance
“…In line with previous research, greater levels of collective guilt were associated with a greater likelihood to engage in bystander anti-racism (e.g., Doosje et al, 1998;Halloran, 2007;Pedersen & Thomas, 2012), as was greater empathic concern (e.g., Eisenberg & Miller, 1987;Karancanta & Fitness, 2006;Pedersen & Thomas, 2012;Oswald, 1996). In other words, participants who experienced higher levels of guilt on behalf of their ingroup with respect to the past and present mistreatment of Indigenous Australians, and who reported greater levels of concern for the welfare of Indigenous Australians, were more likely to speak up against their discrimination.…”
Section: Correlates Of Bystander Anti-racism Intentions (Aim 1)supporting
confidence: 88%
See 1 more Smart Citation
“…In line with previous research, greater levels of collective guilt were associated with a greater likelihood to engage in bystander anti-racism (e.g., Doosje et al, 1998;Halloran, 2007;Pedersen & Thomas, 2012), as was greater empathic concern (e.g., Eisenberg & Miller, 1987;Karancanta & Fitness, 2006;Pedersen & Thomas, 2012;Oswald, 1996). In other words, participants who experienced higher levels of guilt on behalf of their ingroup with respect to the past and present mistreatment of Indigenous Australians, and who reported greater levels of concern for the welfare of Indigenous Australians, were more likely to speak up against their discrimination.…”
Section: Correlates Of Bystander Anti-racism Intentions (Aim 1)supporting
confidence: 88%
“…Collective guilt has been shown to predict support for gay and lesbian anti-violence programmes (Karacanta & Fitness, 2006), the compensation of Indonesians in regards to disadvantage ensuing from Dutch colonisation (Doosje et al, 1998), government apology with respect to Australia's history of discrimination towards Indigenous Australians (McGarty et al, 2005, Studies 1 and 2), reconciliatory attitudes and behaviours within the context of Indigenous Australian history (Halloran, 2007), and reparation attitudes with respect to the Indigenous Chilean history (Brown, Gonzalez, Zagefka, Manzi, & Cehajic, 2008). More recently, Pedersen and Thomas (2012) reported that collective guilt was one of the two emotions most cited by participants when reading about racial discrimination scenarios.…”
Section: Collective Guiltmentioning
confidence: 99%
“…Intragrupalmente, la exposición de los jóvenes a la violencia colectiva se ha relacionado con cambios interpersonales vinculados con la solidaridad y benevolencia endogrupal y un mayor compromiso con la ideología política dominante (Calderón Prada, Espinosa & Techio, 2004;Conejero & Etxebarria, 2007). Halloran (2007), además, encontró que valores igualitarios, universalistas y de baja conformidad funcionarían como predictores de la reconciliación intergrupal, especialmente ante identidades salientes en espacios de contacto intergrupal. Por último, investigaciones en contextos que experimentaron violencia colectiva reportan en las personas preponderancia de valores de orientación social, así como también valores de auto-trascendencia e indicadores de crecimiento psicológico (Cárdenas et al, 2014;Vázquez & Páez, 2010).…”
Section: Bienestar Valores Y Clima Emocionalunclassified
“…En base a la evidencia empírica revisada preliminarmente y al contexto en el que se llevó a cabo el estudio, se planteó como hipótesis que los valores de motivación humanitaria y de orientación central y social tienen una influencia directa en el SWB, el BS y el clima emocional positivo Halloran, 2007;Sagiv & Schwartz, 2000).…”
Section: Objetivo E Hipótesis Del Estudiounclassified
“…This manipulation has been used successfully in previous research to manipulate relative identity salience (e.g. Adarves-Yorno, Postmes, & Haslam, 2006;Halloran, 2007). 1 1 Given the close nesting of identities used in this study, a follow-up study was conducted to check the effectiveness of the identity salience manipulation in manipulating relative salience.…”
mentioning
confidence: 96%